Pest Control in Organic Farming - Costa, Cristina Amaro Da (2018)
Organic farming is an environmentally friendly farming system that produces food based on the ecological balance of ecosystems, preventing soil fertility decline or pest problems. It is a proactive alternate approach to intensive agriculture, minimizing its adverse effects and contributing to maintaining soil quality and enhancing biodiversity. Pests represent a threat to crops, causing important damage and economic losses, and therefore they must be controlled. This is especially relevant in organic farming, where the environment and human health should be protected and thus the methods available for pest management are limited. When intervention against pests is necessary, farmers can either use preventive actions or direct control methods, always based on a weighted decision-making process. Regarding the options for pest management, there are often different possibilities, which may vary in efficacy, resource-intensiveness, knowledge and technical skills, and risk. For this reason, risk assessment is essential for efficient use of the available resources and crop protection strategies. This chapter aims to cover different strategies of pest and disease control, from preventive methods to direct intervention methods of different natures.